Platelet Lymphocyte Ratio (Prl) And Grace (Global Registry Of Acute Coronary Events) Score As Prognostic Indicators Of Mortality In Acute Coronary Syndrome - Novia Alisa; Teuku Rahadiyan; Ahmad Syauqi (Asosiasi Dosen Muda Indonesia, 2025)
Inflammation plays a crucial role in the early stages of atherosclerosis, which can then trigger acute coronary syndrome. Acute coronary syndrome (ACS) is a potentially fatal condition. Therefore, accurate predictive tools are needed to estimate mortality risk, allowing for more appropriate patient management. One commonly used method is the GRACE (Global Registry of Acute Coronary Events) score. Several studies have shown that combining the GRACE score with clinical and laboratory parameters can improve the accuracy of mortality prediction in ACS patients. In this regard, an easily obtained and assessed inflammatory indicator. the Platelet-Lymphocyte Ratio (PRL), can be an effective tool. This study is observational analytics with a retrospective approach. This study included 98 patients with a diagnosis of ACS based on medical record data. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS). P-value <0.05 was considered statistically significant. A chi-square statistical test was performed on mortality rate (p-value=<0.001). The same test was performed on the Grace score on mortality (p-value=<0.001). These findings indicate that both RPL and GRACE score can be used as effective prognostic indicators of mortality in patients with acute coronary syndrome.